(3GdhLjR aj TQM GdbGfhf GdeOfj (B:s (3GdMbhb GdYjfjI, GdMbhb GdYjfjI GdCUdjI, GdMbhb GdYjfjI GdJHYjI, Mb GdedcjI, GdMbhb GdeJaQYI Yf Mb GdedcjI (B: (3OQGSI ehGRfI (B= The digest commentary on civil law real eights : original real rights-consequential real rights ownership property right a comparative study /s - (3GdYHjOj, Ydj gGOjs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2017)
(3jJfGhd cJGH (B((3GdhLjR aj TQM GdbGfhf GdeOfj(B) (3hGdPj bGe HJCdjag (B((3Ydj gGOj GdYHjOj(B) (3aj MhGdj (B(349) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdbGfhf GdeOfj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3ebOeI, JegjO, GdcJGH GdChd (B: (3GdMbhb GdYjfjI GdCUdjI, hjTed GdHGH GdChd (B: (3Mb GdedcjI, GdHGH GdKGfj (B: (3GdMbhb GdeJaQYI Yf Mb GdedcjI(B. (3GdcJGH GdKGfj (B: (3GdMbhb GdYjfjI, GdJHYjI, GdJCejfGJ GdYjfjI, hjTed GdHGH GdChd (B: (3GdQgf GdJCejfj, GdHGH GdKGfj (B: (3GdQgf GdMjGRj(B.s
Keywords: (3GdbGfhf GdeOfjs -- (3GdCQOfs; (3GdMbhb GdYjfjI GdJHYjIs -- (3GdCQOfs; (3Mb GdedcjIs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs